2004
DOI: 10.1007/s00167-003-0465-5
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic overload or acute syndrome of the os trigonum: a possible cause of posterior ankle impingement

Abstract: IntroductionOs trigonum syndrome is often ignored in findings that can result in hind-foot pain. It results from numerous disorders and may in fact be associated with an os trigonum or posterior trigonal process.The differential diagnosis of this condition includes flexor hallucis longus tenosynovitis, peroneal tenosynovitis and tendinitis, intraarticular loose bodies and ankle synovitis [2,7,8,10,11,12,14,15,18].This pathology is frequently encountered in athletes such as ballet dancers, soccer players, javel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Displaced fractures can be managed with arthroscopic and/or open surgery to fix or excise the fracture fragment [ 3 ]. Treatment of PAIS related to os trigonum can be managed nonoperatively with activity modification, physical therapy, and corticosteroid injection with success in up to 84% of cases [ 14 ]. Nonoperative management was the plan for the last case we described.…”
Section: Discussionmentioning
confidence: 99%
“…Displaced fractures can be managed with arthroscopic and/or open surgery to fix or excise the fracture fragment [ 3 ]. Treatment of PAIS related to os trigonum can be managed nonoperatively with activity modification, physical therapy, and corticosteroid injection with success in up to 84% of cases [ 14 ]. Nonoperative management was the plan for the last case we described.…”
Section: Discussionmentioning
confidence: 99%
“…4,24 Therefore, all patients continued conservative therapy for 6 mo. Although some authors would argue that local steroid injection has been found to be successful in relieving pain; 25 others, with whom the authors agree, discourage the use of corticosteroids injection in athletic patients because of the potential harmful effects on the posterior ankle structures. 4,23,24 Existing operative options for failed conservative therapy include posterior ankle endoscopy, subtalar arthroscopy, and open resection through posteromedial or posterolateral approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, all patients continued conservative therapy for 6 mo. Although some authors would argue that local steroid injection has been found to be successful in relieving pain;25 others, with whom the authors agree, discourage the use of corticosteroids injection in athletic patients because of the potential harmful effects on the posterior ankle structures 4,23,24…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroid and anesthetic injection into a posterolateral capsule abnormality in athletes with clinical posterior impingement with ultrasonography guidance showed good results and rapid return to athletic activity in football players. 16 , 17 USG-guided corticosteroid injection for 12 patients who did not experience any improvement or even worsen with conservative treatment after 4 weeks was performed. However, symptomatic relief with corticosteroid injection was significantly lower in our group compared with the previous studies.…”
Section: Discussionmentioning
confidence: 99%